Software quality engineering : Testing, quality assurance, and quantifiable improvement - Tian, Jeff. (Hoboken, N.J. : Wiley, 2005)
"This text offers a comprehensive and integrated approach to software quality engineering. By following the author's clear guidance, readers learn how to master the techniques to produce high-quality, reliable software, regardless of the software system's level of complexity." "This is a superior textbook for software engineering, computer science, information systems, and electrical engineering students, and a dependable reference for software and computer professionals and engineers."--Jacket
What is software quality? -- Quality assurance -- Quality assurance in context -- Quality engineering -- Testing : concepts, issues, and techniques -- Test activities, management, and automation -- Coverage and usage testing based on checklists and partitions -- Input domain partitioning and boundary testing -- Coverage and usage testing based on finite-state machines and Markov chains -- Control flow, data dependency, and interaction testing -- Testing techniques : adaptation, specialization, and integration -- Defect prevention and process improvement -- Software inspection -- Formal verification -- Fault tolerance and failure containment -- Comparing quality assurance techniques and activities -- Feedback loop and activities for quantifiable quality improvement -- Quality models and measurements -- Defect classification and analysis -- Risk identification for quantifiable quality improvement -- Software reliability engineering.
"IEEE; IEEE Computer Society."
Includes bibliographical references (pages 389-402) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Computer software -- Quality control; Computer software -- Testing; Logiciels -- x; REFERENCE -- General; Computer software -- Quality control; Computer software -- Testing; Electrical and Electronics Engineering